ChemInform Abstract: Asymmetric Phase‐Transfer Catalysts Bearing Multiple Hydrogen‐Bonding Donors: Highly Efficient Catalysts for Enantio‐ and Diastereoselective Nitro‐Mannich Reaction of Amidosulfones. Issue 22 (15th May 2015) - Wang, Bin; Liu, Yuxin; Sun, Cong; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Abstract: A new class of bifunctional phase‐transfer catalysts derived from cinchona alkaloids and various β‐amino alcohols are prepared and applied in the title reaction.